2013
DOI: 10.3945/ajcn.113.058313
|View full text |Cite
|
Sign up to set email alerts
|

Tea, flavonoids, and cardiovascular health: endothelial protection

Abstract: Several studies have suggested that tea consumption might protect against the development and progression of cardiovascular disease, one of the leading causes of morbidity and mortality worldwide. The endothelium plays a pivotal role in arterial homeostasis. Reduced nitric oxide (NO) bioavailability with endothelial dysfunction is considered the earliest step in the pathogenesis of atherosclerosis. Endothelial dysfunction has been considered an important and independent predictor of future development of cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 54 publications
0
66
0
Order By: Relevance
“…Flavonoids have repeatedly been shown to improve cardiovascular diseases including hypertension, ischemic heart disease, and stroke (Hertog et al, 1993;Keli et al, 1996;Perez-Vizcaino et al, 2009). It has been further shown that flavonoids protect and improve endothelial function (Engler et al, 2004;Vita, 2005;Hodgson, 2006;Grassi et al, 2013). This is of considerable importance because endothelial dysfunction is a hallmark of most types of cardiovascular disease, including hypertension, diabetes, atherosclerosis, and ischemic heart disease (Hadi et al, 2005;Vita, 2005;Deanfield et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids have repeatedly been shown to improve cardiovascular diseases including hypertension, ischemic heart disease, and stroke (Hertog et al, 1993;Keli et al, 1996;Perez-Vizcaino et al, 2009). It has been further shown that flavonoids protect and improve endothelial function (Engler et al, 2004;Vita, 2005;Hodgson, 2006;Grassi et al, 2013). This is of considerable importance because endothelial dysfunction is a hallmark of most types of cardiovascular disease, including hypertension, diabetes, atherosclerosis, and ischemic heart disease (Hadi et al, 2005;Vita, 2005;Deanfield et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] As a result, catechin and EGCG have attracted the interest of researchers and manufacturers, and these natural molecules are considered to be promising drug candidates in the pharmaceutical, cosmetic, and nutritional fields. They have already been used in the food industry as natural additives and have been applied in cosmetic products as antiaging components.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it could help to protect against the development and progression of cardiovascular disease (31). Antioxidant actions would be at the root of its biological activity but other mechanisms could also play an important role (32,33).…”
Section: Discussionmentioning
confidence: 99%